In Search of More Mature Uses of Data: Problematizing Education and Poetry - F. Todd Goodson (Educational Considerations, 2024)
Alex Romagnoli’s article in this issue, a discussion of the use of quantitative metrics in education and baseball, provides a thoughtful discussion the limitations inherent in those metrics as well as ways they can be enhanced to provide more useful information. This manuscript extends Romagnoli’s manuscript with specific illustrations of the ways grade point averages can be interpreted in context along with a call for a much more nuanced approach to data by policy makers and decision makers.
Keywords: Assessment; policy